Association of polysocial risk score, cardiovascular health status, and the risk of premature mortality: Findings from the UK Biobank - Wenqi Shen; Lingli Cai; Bin Wang; Jiang Li; Ying Sun; Ningjian Wang; Yingli Lu (The Journal of Nutrition, Health and Aging)
Background: Evidence of the cumulative effects of social risk factors on premature mortality is quite limited. We aimed to examine the association between cumulative social risk factors and premature mortality by constructing a polysocial risk score, and to explore the influence of cardiovascular health on this association. Methods: A polysocial risk score was constructed by summing 11 social determinants of health. A cardiovascular health (CVH) score was calculated following the algorithm of ''Life’s Essential 8”. Premature mortality was defined as death at an age younger than 75. Cox proportional hazards model was conducted. Results: A total of 314,039 participants in the UK Biobank were included (median age 56.0 years, 53.1% women). During a median of 12.7 years of follow-up, 13,888 premature deaths were reported. Compared with participants who had a low polysocial risk score (≤3), participants with a high polysocial risk score (≥7) were more than twice as likely to die prematurely in the follow-up period (HR 2.18, 95% CI 2.06–2.30). Compared with participants with ideal CVH and low polysocial risk score, those with poor CVH and high polysocial risk score had the highest risk of premature mortality (HR 5.25, 95% CI 4.48–6.14). A significant interaction was found between CVH status and polysocial risk score on premature mortality risk (P for interaction <0.001). Conclusions: Polysocial risk score was associated with an increased risk of premature mortality, the association was exacerbated by poor CVH. Our findings indicate that limiting social inequities and encouraging people to achieve an ideal CVH are essential to reducing the burden of premature mortality.